Using Media to Stimulate Babies’ Language Activities Development - Ulfa, Kurnia (Majalah Ilmiah METHODA, 2024)
As the digital age continues to reshape educational paradigms, it is essential to investigate the purposeful integration of media into infants’ lives to enhance language acquisition “Harmonizing Voices” explores how age-appropriate media, such as videos, apps, and interactive content, can complement traditional methods, providing infants with a multi-sensory and engaging platform for language exploration. Today, various strategies are employed to stimulate babies from pregnancy through infancy, with mothers increasingly using media as a tool. This includes playing music during pregnancy and introducing nursery rhymes through media post-birth to create a sensory -rich environment. This study investigates the synergy between the melodic allure of English nursery rhymes and intricate process of a baby’s linguistic development. Digital platforms like YouTube and Netflix offer numerous nursery rhymes, such as Cocomelon and Bebefinn, which are popular among infants. This research aims to evaluate which of these nursery rhymes programs is more effective in stimulating infants and which elicits more positive reactions. Caregivers, educators, and researchers will gain insights into the connections between musicality, language and early cognitive development through this exploration. The study addresses the identification of high quality media content, strategies for joint engagement between caregivers and infants, and the potential impact of media on various facets of language development. By fostering an environment where technology harmonizes with natural language acquisition processes, this research aspires to contribute valuable insights for educators, caregivers, and researchers. The objective of this study is to observe and compare infants’ reactions to two popular nursery rhyme programs, Cocomelon and Bebefinn. The research aims to identify which program stimulates more positive engagement, thereby providing a deeper understanding of infants’ preferences and the effectiveness of media content in early language development.